2018
DOI: 10.4012/dmj.2016-411
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation effectiveness of continuous ultrasonic irrigation system: An <i>ex vivo</i> study

Abstract: This study evaluated the irrigation extrusion and smear layer (SL) removal of continuous ultrasonic irrigation (CUI). Forty root canals were shaped, embedded in warm sterile saline agar colored with 1% acid red, and distributed into four groups; three groups had the final irrigation sequence of sodium hypochlorite and EDTA solutions performed by using syringe irrigation (SI), EndoVac (EV), and CUI, respectively. Group 4 had the canals ultrasonically irrigated with saline (CUIS). Irrigant extrusion was verified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…If the calculated criterion is less than the tabular one for the corresponding degrees of freedom (d.o.f.) [21][22][23][24] …”
Section: Resultsmentioning
confidence: 99%
“…If the calculated criterion is less than the tabular one for the corresponding degrees of freedom (d.o.f.) [21][22][23][24] …”
Section: Resultsmentioning
confidence: 99%
“…This may be related to the fact that histological studies focused primarily on debris removal in the apical region. Previous studies [ 12 , 17 , 51 ] reported that the AHTD removal efficacy of EndoVac was better than SNI and PUI in the apical region; specifically, it was better than SNI at 1 mm from WL and comparable to PUI at 1 mm and 3 mm [ 52 ]. Our study may imply that the negative pressure system improves the cleaning efficiency of the apical region at the expense of the cleaning efficiency of the pulp cavity and isthmus.…”
Section: Discussionmentioning
confidence: 99%
“…E. faecalis has been used in several previous studies that examined the efficacy of irrigant and dressing materials within root canals [ 18 ]. The apical foramen of teeth was closed with composite to transform the inner canal space into a closed system to simulate clinical conditions, and this is what was adopted in this research as a root canal in the presence of the surrounding tissues tends to be a closed-ended system [ 19 ]. The irrigant protocol was standardized in terms of time and volume, as the irrigant time, according to previous studies, ranged between 30 seconds and 10 minutes, while the irrigant volume, according to previous studies, ranged between 0.05 ml and 15 ml.…”
Section: Discussionmentioning
confidence: 99%